Analisis Pertimbangan Hakim Terhadap Pengguna Narkotika Jenis Shabu (Analisis Putusan Mahkamah Agung Nomor 758 K/Pid.Sus/2020) - Adi Ariandi (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2022)
Law enforcement against narcotics crimes has been widely carried out by law enforcers, as well as many perpetrators who have been sentenced to court decisions and are serving sentences in correctional institutions. The formulation of the problem in this thesis is how to regulate criminal law/sanctions against users of shabu-shabu narcotics, how to apply criminal sanctions to users of shabu-shabu narcotics, how the judge's legal considerations impose sanctions on users of shabu-shabu narcotics in the decision of the Supreme Court Number 758 K/Pid.Sus/2020. The results of the study indicate that the regulation of criminal law/sanctions against users of shabu-shabu narcotics based on Law Number 35 of 2009 concerning Narcotics prioritizes rehabilitation of narcotics users, but the criminal sanctions against drug dealers and precursors are very high. The spirit and purpose of Law Number 35 of 2009 concerning Narcotics is to prevent and eradicate illicit narcotics trafficking in Indonesia. The application of criminal sanctions against users of methamphetamine type narcotics is that the defendant is imposed with a criminal sanction in the form of imprisonment for 1 (one) year and 6 (six) months and a fine of Rp. 800,000,000.00 (eight hundred million rupiah) provided that if the fine is If not paid, it will be replaced with imprisonment for 2 (two) months. The judge's legal considerations for imposing sanctions on users of shabu-shabu narcotics in the Supreme Court's decision Number 758 K/Pid.Sus/2020 are in accordance with the subsidiary indictment of the Public Prosecutor and have fulfilled the elements of Article 112 paragraph (1) of Law No. 35 of 2009 concerning Narcotics and there is no justification and excuse for the actions committed by the defendant. Keywords: Judge's Consideration, Narcotics, Shabu.